2015
DOI: 10.1039/c4gc01631a
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of chitin derived N-acetyl-d-glucosamine (NAG) into polyols over transition metal catalysts and hydrogen in water

Abstract: N-Acetyl-D-glucosamine (NAG), the monomer of the world's second most abundant biopolymer chitin, has been for the first time converted to its corresponding amide/amino substituted sugar alcohols, smaller C2-4 polyols and N-acetylmonoethanolamine (NMEA), over noble metal catalysts in the presence of hydrogen in water. Four commercialized catalysts were investigated, and Ru/C exhibited the best performance-achieving 8.7% NMEA, 6.1% C4 polyols, and 71.9% C6 polyols (N-containing) under 180°C, 40 bar H 2 , 1 h wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 80 publications
0
92
0
Order By: Relevance
“…However, chitin biomass, which is the second most abundant biomass, has received much less attention and has therefore not been widely studied for biomass utilization Nam, Park, Ihm, & Hudson, 2010;Ou et al, 2010;Stolarek & Ledakowicz, 2005;Taboada, Cabrera, Jimenez, & Cardenas, 2009;Tang et al, 2005;Zeng et al, 2011). It has been reported that chitin biomass, including these biopolymers (chitin and chitosan) and corresponding monosaccharides N-Acetyl-d-glucosamine and d-glucosamine), could produce hydroxyethyl-2-amino-2-deoxyhexopyranoside, levulinic acid, 5-hydroxymethylfurfural, 3-acetamido-5-acetylfuran, polyols and other compounds in solution phase (Bobbink, Zhang, Pierson, Chen, & Yan, 2015;Chen, Chew, Kerton, & Yan, 2014;Chen, Liu, Kerton, & Yan, 2015;Mascal & Nikitin, 2009;Omari, Besaw, & Kerton, 2012;Pierson, Chen, Bobbink, Zhang, & Yan, 2014;Wang, Pedersen, Deng, Qiao, & Hou, 2013). Our recent investigation also showed that glucosamine, the monomer of chitosan, could convert into nitrogen-containing chemicals, such as deoxyfructosazine (DOF) and fructosazine (FZ), in a homogeneous system (Jia, Wang, Qiao, Qi, & Hou, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…However, chitin biomass, which is the second most abundant biomass, has received much less attention and has therefore not been widely studied for biomass utilization Nam, Park, Ihm, & Hudson, 2010;Ou et al, 2010;Stolarek & Ledakowicz, 2005;Taboada, Cabrera, Jimenez, & Cardenas, 2009;Tang et al, 2005;Zeng et al, 2011). It has been reported that chitin biomass, including these biopolymers (chitin and chitosan) and corresponding monosaccharides N-Acetyl-d-glucosamine and d-glucosamine), could produce hydroxyethyl-2-amino-2-deoxyhexopyranoside, levulinic acid, 5-hydroxymethylfurfural, 3-acetamido-5-acetylfuran, polyols and other compounds in solution phase (Bobbink, Zhang, Pierson, Chen, & Yan, 2015;Chen, Chew, Kerton, & Yan, 2014;Chen, Liu, Kerton, & Yan, 2015;Mascal & Nikitin, 2009;Omari, Besaw, & Kerton, 2012;Pierson, Chen, Bobbink, Zhang, & Yan, 2014;Wang, Pedersen, Deng, Qiao, & Hou, 2013). Our recent investigation also showed that glucosamine, the monomer of chitosan, could convert into nitrogen-containing chemicals, such as deoxyfructosazine (DOF) and fructosazine (FZ), in a homogeneous system (Jia, Wang, Qiao, Qi, & Hou, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…We performed the reaction at a low temperature of 393 K, because a lower temperature generally gives higher selectivity in hydrogenation of sugars. 16,32 Reduction of NAG to ADS proceeded in a first-order manner in the presence of Ru/TiO 2 and 4 MPa of H 2 (Fig. 3a).…”
Section: Two-step Hydrolytic Hydrogenation Of Oligomer-h 2 Somentioning
confidence: 99%
“…However, ADS was only synthesised from pure NAG, and ADS was not obtained from chitin previously. 16 Herein, we demonstrate the first catalytic conversion of chitin to ADS (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under 180 °C, 40 bar H 2 with 1 mol% loading of Ru/C, 71.9 % of C6 N‐containing polyols, 6.1 % C4 polyols and 8.7 % N‐acetylmonoethanolamine (NMEA) were produced. Through the kinetic studies, the mechanistic pathway was proposed which confirmed the formation of NMEA through retro aldol condensation (Scheme ) …”
Section: N‐containing Biopolymers As a Source Of Platform Chemicalsmentioning
confidence: 97%